The experience of Romanian physiotherapists in the management of postoperative rehabilitation of patients with total hip arthroplasty - content and criteria for completion of physiotherapy sessions - Marjan Mihajlov; Ilie Onu; Dan Trofin; Laurențiu Gabriel Talaghir; Daniel Mădălin Coja; Daniel Andrei Iordan; Mihai Constantinescu; Carmina Liana Musat (Balneo and PRM Research Journal, 2024)
Background: Total hip arthroplasty (THA) is a procedure that removes damaged bone and car-tilage and replaces it with prosthetic components and is performed by orthopedics. Objective: management of post-operative rehabilitation of THA patients in terms of content and comple-tion criteria of physiotherapy sessions. The research aims to explore the experience of Romani-an physiotherapists about the content and completion criteria of physiotherapy sessions in-volved in the management of postoperative rehabilitation after THA. Methods: The method used in this study was a questionnaire-based survey, with 120 Romanian specialists in the field completing an online screening tool that contained, along with a socio-demographic question-naire, a series of questions about their professional experience. Results: One of the most im-portant results of the study is the identification of statistically significant associations between the completion criteria of physiotherapy sessions and three techniques included in the rehabil-itation program after THA: edema management, gait re-education exercises, and exercises to increase hip mobility. Conclusion: The the research revealed that the experience of Romanian specialists regarding postoperative rehabilitation after THA is concordant with the experience of specialists in the field, and can be used to develop and test an individualized therapeutic protocol and to design continuing professional training programs for physiotherapists in Romania.